Pain following stroke: a population-based follow-up study. - Henriette Klit (Public Library of Science (PLoS), 2011)
Background and purpose Chronic pain is increasingly recognized as a consequence of stroke. This study aimed to describe the prevalence and pain types of new onset chronic pain ("novel pain") in patients with stroke compared with a randomly selected reference group from the general population and to identify factors associated with pain development in stroke patients. Methods In a population-based follow-up design, development of chronic pain after stroke was assessed by a questionnaire sent to consecutive stroke patients, registered in a Danish national stroke database, two years after their stroke. A randomly selected sex- and age-matched reference group from the same catchment area received a similar questionnaire about development of new types of chronic pain in the same time period. A total of 608 stroke patients and 519 reference subjects were included in the study. Results Development of novel pain was reported by 39.0% of stroke patients and 28.9% of reference subjects (OR 1.57, CI 1.21-2.04), and was associated with low age and depression in a multivariate model. Daily intake of pain medication for novel pain was reported by 15.3% and 9.4% of the stroke and reference population, respectively. Novel headache, shoulder pain, pain from increased muscle stiffness, and other types of novel pain were more common in stroke patients, whereas joint pain was equally common in the two groups. Conclusions Development of chronic pain is more common in stroke patients compared with sex- and age-matched reference subjects. Evaluation of post-stroke pain should be part of stroke follow-up.